Comparative study of magnetic Pc 1 pulsations observed at low and high latitudes: Source region and generation mechanism of periodic hydromagnetic emissions - Kawamura, Makoto; Kuwashima, Masayuki; Toya, Takeshi (1982)
P(論文) Main purposes of this study are to identify the source region and generation mechanism of periodic emissions by comparison of the characteristics of emissions observed at high and low latitudes. In the present paper, the periodic emissions observed at Syowa Station and Memambetsu for a two-year period from January 1977 to December 1978 are studied. Relations of the occurrence to the magnetic activity Dst and also Kp dependence of the mean frequency are investigated statistically. Periodic emissions are closely related to development of the equatorial ring current and tend to occur during the recovery phase of an intense magnetic storm. The occurrence peaks are observed on the second or third day after the maximum Dst at low latitudes, and two days later at auroral latitudes. This suggests that the occurrence depends on the conditions of the Dst development. The emissions are observed usually only at low latitudes in case of a sharp and distinct development of the Dst. While, in case of gradual storm development, the emissions occur at rather high latitudes. These results indicate that the source region of the emissions may be located near the plasmapause and that the plasmapause position shifts gradually outwards with the lapse of storm-time. In addition, the emissions are subjected to an intense attenuation through ionospheric duct propagation. On the other hand, mean frequency of the emissions is higher at low latitudes than at high latitudes. At both latitudes the emission frequency (Hz) shows a characteristic diurnal variation with a maximum at about 06 LT, specially in disturbed conditions. These facts will support the above-described interpretation. If resonance frequency becomes lower with an outward shift of the plasmapause, the above characteristics of the mean frequency will also suggest that the source of the emissions is the plasmapause and the frequency reflects the size and the configuration of the plasmapause. Assuming that the source region of the periodic emissions is near the ...